THE ROLE OF SMALL BUSINESS AND ENTREPRENEURSHIP IN THE ECONOMY - Nasirov Mansur Ibroximovich (American Journals, 2023)
The current stage of economic reforms implemented in our country requires the development of small business and private entrepreneurship, giving it wide economic freedom and improving its efficiency. In order to achieve this goal, the development of a number of decrees and decisions by the head of our country will definitely serve to increase the efficiency of small business and private entrepreneurship.
Keywords: Business, Economic indicators, e-commerce, GDP, sustainable development.